Uncovering a Protease in Snake Venom Capable To Coagulate Milk to Curd - Jaya Vejayan, Palliah; Amira Alia, Zulkifli; Syed Mohd Saufi, Tuan Chik; Norliana, Munir; Ambu, Stephen; Halijah, Ibrahim (BioIT, 2017)
Snake venom been studied for its lethality and various benefits for mankind. The latter been studied a plenty of recent but none related to coagulation of milk to curd. The coagulation time of milk by samples were done using visible parameters i.e. change in viscosity, colour changes, white spot formation (separation between curd and whey) and finally observing a drop of coagulating fluid under magnification of a light microscope. Optimum parameters determined included concentration of coagulants, temperature and pH. Microscopic viewing included observing after centrifugation, under light microscope and SEM. Screening eleven venoms mostly predominantly found in tropical region singled out one with the most rapid coagulating timei.e by Calloselasma rhodostoma (CR). Optimization of CR venom related to several parameters provided venom concentration, 0.07 (w/v%); pH,7.0; temperature, 45.50C while that of rennet were determined to be 0.04±0.02 (w/v%); pH,7.0; temperature, 45.50C, respectively. Under these ideal conditions for both coagulants, comparison of their milk coagulation time found CR superior i.e. 0.41±0.02 min compared to 4.23±0.05 min for rennet. Milk coagulating assay guided fractionation of CR venom by using HiTrap SP FF and consecutively followed by HiPrep 26/60 Sephacryl S200 HR pre-packed columns led to a single band on coomassie stained SDS-PAGE gel. Next by LCMS analysis on the SDS PAGE band identified the presence of metalloproteinase kistominwithin the venom. EDTA inactivated the venom presumably chelating zinc hence suggesting further towards identifying kistomin as the likely protease within this venom with milk-clotting activity. Snake venom been potentially identified for yet another application for the benefit of mankind. In this investigation Malayan Pit Viper’s protease can play major role in dairy industry if studied further.